2019
DOI: 10.1002/cam4.2030
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of pelvic fracture after radiotherapy in rectal cancer survivors: A propensity matched study

Abstract: To determine whether radiotherapy ( RT ) can increase pelvic fracture risk in rectal cancer survivors. Rectal cancer patients who underwent curative surgery between 1996 and 2011 in Taiwan were retrospectively studied using the National Health Insurance Research Database ( NHIRD ) of Taiwan. ICD ‐9 Codes 808, 805.4‐805.7, 806.4‐806.7, and 820 (including pelvic, sacrum, lumbar, and femoral neck fracture) were defined as pelvic fracture. Propen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…However, it can be misinterpreted as local recurrence. Improvement in radiotherapy technique reduces the risk of IF in rectal cancer survivors [6]. MRI scans are recommended to make accurate diagnosis of IF.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it can be misinterpreted as local recurrence. Improvement in radiotherapy technique reduces the risk of IF in rectal cancer survivors [6]. MRI scans are recommended to make accurate diagnosis of IF.…”
Section: Resultsmentioning
confidence: 99%
“…Pelvic insufficiency fracture is detected in 3.3-7.1% of cases after radiotherapy, and can be noted between 2 months to 8 years after treatment [4]. A study performed by Yu-Mei Kang et al [6], confirmed that pelvic fracture risk is higher after 2-4 years of follow-up after RT. On this case, it is advised that physicians pay more attention to pelvic fractures during the first four years of follow-up among rectal cancer patients who receive pelvic RT.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We found an association between cortical thinning and reduced fatigue life that was only significant within all the 12-week groups. It has been shown that the incidence of insufficiency fractures post-radiotherapy increases after 1 year (2) and that the median time to fracture after treatment is approximately 2.5 years (4) . Taken together, these findings would question the role of irradiation alone, and consider the role of irradiation plus time on insufficiency fractures (24)(25)(26)(27) such as those following radiation therapy, which have been reported to occur after repetitive loading at magnitudes well below the bone's strength (57,58) .…”
Section: Discussionmentioning
confidence: 99%
“…The effects of exposure to ionizing radiation on bone strength is of interest for numerous reasons, including oncologic radiotherapy and space exploration, among others. Following oncologic radiotherapy, fragility fractures in cancer survivors are a known complication (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) . For example, the risk of hip insufficiency fracture in postmenopausal women treated for cervical, rectal, or anal cancer (9) or in men treated for prostate cancer (10) is increased at sites directly exposed to radiation (relative risk: 1.66, 1.65, 3.14, and 1.76, respectively).…”
Section: Introductionmentioning
confidence: 99%